2019
DOI: 10.1051/e3sconf/201913607017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc Fertilizer on Photosynthetic Characteristics of 'Shine Muscat' Grape

Abstract: Zinc is an essential nutrient for plant growth and development. Zinc deficiency affects plant photosynthesis and nitrogen metabolism. In this experiment, 'Shine Muscat' grape was used as experimental material. Three soil application levels of zinc sulfate were set up, which were 2 kg/667 m2, 3 kg/667 m2 and 4 kg/667 m2, respectively. The time of applying zinc fertilizer in soil was 10 days after flowering, and the time of spraying zinc fertilizer was divided into 21 days after flowering, 35 days after flowerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
1
1
0
Order By: Relevance
“…According to [23,24], fertilization with sources of Zn, lead to an increase in this mineral's concentration in leaves of Pistachio trees, in sweet orange and Feutrell's early mandarin plants. Furthermore, in a study with a grape variety, 'Shine Muscat', this increase was observed after Zn fertilization through foliar and soil application [25]. Data of Zn content in leaves obtained in this study are in agreement with the other works previously mentioned, revealing an increase in Zn content in leaves after three foliar applications with both treatments (ZnSO 4 or ZnO), prevailing a higher rise with treatment ZnSO 4 (Figure 2).…”
Section: Discussionsupporting
confidence: 91%
“…According to [23,24], fertilization with sources of Zn, lead to an increase in this mineral's concentration in leaves of Pistachio trees, in sweet orange and Feutrell's early mandarin plants. Furthermore, in a study with a grape variety, 'Shine Muscat', this increase was observed after Zn fertilization through foliar and soil application [25]. Data of Zn content in leaves obtained in this study are in agreement with the other works previously mentioned, revealing an increase in Zn content in leaves after three foliar applications with both treatments (ZnSO 4 or ZnO), prevailing a higher rise with treatment ZnSO 4 (Figure 2).…”
Section: Discussionsupporting
confidence: 91%
“…'샤인머스캣' 포도의 수확기준을 설정하기 위한 칼라차트가 개발되었으며 (Yamada et al, 2008;Kim et al, 2019a), 휘발성 물질에 관한 연구 (Wu et al, 2020), 호르몬 처리에 의한 과실의 변화 (Suehiro et al, 2019), 비료에 의한 과실의 특성 변화 (Yao et al, 2019), 곰팡이에 의한 썩음병에 관한 연구 (Kim et al, 2019b), 기온에 따른 열과 발생에 관한 연구 (Kim et al, 2021) 등 과실에 대한 실험은 다양하게 진행되었지만 그 외의 기관을 대상으로 한 연구는 매우 부족한 실정이다. 특히 신초에 꽃송이가 생기지 않는 빈가지 발생은 '샤인머스캣' 포도에서 종종 문제가 되고 있으나 거의 연구된 바가 없다.…”
unclassified
“…Zn deficiency triggers the accumulation of saccharides, particularly in phloem sap leaves, which might be associated by decrease in CO 2 fixation. Net photosynthetic rate, stomatal conductance and transpiration rate are strongly reduced by Zn deficiency(Das and Mukherjee 2012;Yao et al 2019;Liu et al 2019). Zn plays an important role in the regulation of photosynthesis, due to its presence in carboxylation enzymes (CEs) and carbonic anhydrase (CA) (EC: 4.2.1.1).…”
mentioning
confidence: 99%